PENINGKATAN EFISIENSI PROSES PRODUKSI STICK FUNGSIONAL ANEKA RASA DI KOTA BATU - Arie Febrianto Mulyadi (Journal of Innovation and Applied Technology, 2016)
ABSTRACTThe business of snack food is an prospective of a business that is most preferred by many people because it does not need a lot of capital, simple, and profitable. In Batu city, there are two members of SMEs that produce stick functional are KHARIS and LUBER REJEKI. The advantages of this snack food can be consumed by all segments of consumers with affordable prices and safe for consumption. During the 2nd SMEs doing the majority of the production of onion stick manually, especially in the process of mixing and shaping of stick are not maximum production capacity, only 5 kg per hour. These activities include the dissemination methods of production equipment technology such as Food Mixer and Shaping of Stick Automatic and mentoring of GMP. The results showed that facilitation Food Mixer and Shaping of Stick Automatic can improve the efficiency of 2-4 times, as well as the level of understanding of GMP for SMEs are better.